PEDAGOGICAL SOFTWARE TOOLS FOR FUTURE PRIMARY SCHOOL TEACHERS THEORETICAL AND METHODOLOGICAL FOUNDATIONS OF DEVELOPING CREATIVE SKILLS - Zhuginisova, Zh.I. (SCIENCE and SOCIETY, 2026)
This article illuminates the theoretical and methodological foundations for developing pedagogical software tools (PPV) skills in future primary school teachers. Within the framework of the ADDIE model, the methodological significance of the stages of analysis, design, creation, implementation, and evaluation of pedagogical software tools for primary education has been revealed.
Keywords: primary education; future primary school teacher; pedagogical software tools (PDV); digital education; pedagogical competence; ADDIE model; TPACK model; SAMR model; DigCompEdu; integrative approach; digital pedagogy